Volumetric Prefrontal Cortex Alterations in Patients With Alcohol Dependence and the Involvement of Self‐Control. (5th November 2019) - Rosenthal, Annika; Beck, Anne; Zois, Evangelos; Vollstädt‐Klein, Sabine; Walter, Henrik; Kiefer, Falk; Lohoff, Falk W.; Charlet, Katrin
Abstract : Background: Aspects of self‐control such as sensation seeking and impaired impulse control have been implicated in alcohol dependence (ALC). Conversely, sensation seeking has been ascribed a possible protective role in stress‐related psychopathologies. We therefore examined gray matter (GM) morphology in individuals with ALC, focusing on differences in prefrontal regions that have been associated with self‐control. Additionally, we accounted for differences in lifetime alcohol intake regarding self‐control measures and cortical structures in ALC patients. Methods: With voxel‐based morphometry (VBM) focusing on prefrontal a priori defined regions of interest, we assessed a group of 62 detoxified ALC patients and 62 healthy controls (HC). ALC patients were subsequently divided into high ( n  = 9) and low consumers ( n  = 53). Self‐control was assessed by use of the Barratt Impulsiveness Scale and the Sensation Seeking Scale. Results: Compared to HC, ALC had significantly less GM volume in bilateral middle frontal gyrus (MFG) and right medial prefrontal cortex as well as in the right anterior cingulate. High‐consuming ALC showed smaller GM in right orbitofrontal cortex as well as lower sensation seeking scores than low consumers. In low‐consuming ALC, right MFG‐GM was positively associated with magnitude of sensation seeking; particularly, larger MFG‐GM correlated with greater thrill and adventure seeking. Conclusion: Thus, our findings (i) indicate deficient GM volume in prefrontal areas related to self‐control and (ii) might accentuate the phenotypic divergence of ALC patients and emphasize the importance of the development of individual treatment options. Abstract : In low‐consuming alcohol dependet patients larger middle frontal gyrus grey matter correlated with greater thrill and adventure seeking. In contrast to impulsivity, the trait of thrill and adventure seeking may thus play a protective role in lowering alcohol consumption and preserving prefrontal brain structure. This is consistent with previous findings that sensation seeking behavior may promote resilience to stress, which itself plays a major role in addiction. More broadly the findings highlight differences among individuals with a diagnosis of alcohol dependence.